1992
DOI: 10.1111/j.1365-2958.1992.tb01368.x
|View full text |Cite
|
Sign up to set email alerts
|

A homologue of the Escherichia coli DsbA protein involved in disulphide bond formation is required for enterotoxin biogenesis in Vibrio cholerae

Abstract: A strain of Vibrio cholerae, which had been engineered to express high levels of the non-toxic B subunit (EtxB) of Escherichia coli heat-labile enterotoxin, was subjected to transposon (TnphoA) mutagenesis. Two chromosomal TnphoA insertion mutations of the strain were isolated that showed a severe defect in the amount of EtxB produced. The loci disrupted by TnphoA in the two mutant derivatives were cloned and sequenced, and this revealed that the transposon had inserted at different sites in the same gene. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 41 publications
0
114
0
Order By: Relevance
“…The pathway for CT secretion in V. cholerae includes disulphide bond formation catalysed by the TcpG(DsbA) protein (Yu et al, 1992;Peek and Taylor, 1992), originally identified as a ToxR-regulated gene product (Peterson and Mekalanos, 1988;Peek and Taylor, 1992). A strain deficient for TcpG(DsbA) activity cannot secrete the pentameric B subunit, which is the component of CT that is detected in the GM 1 -ELISA assay (Yu et al, 1992). We hypothesized that if tcpG transcription were under ToxT control, then the mutants might be deficient for CT in the culture supernatants, which is what we use for the GM 1 -ELISA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathway for CT secretion in V. cholerae includes disulphide bond formation catalysed by the TcpG(DsbA) protein (Yu et al, 1992;Peek and Taylor, 1992), originally identified as a ToxR-regulated gene product (Peterson and Mekalanos, 1988;Peek and Taylor, 1992). A strain deficient for TcpG(DsbA) activity cannot secrete the pentameric B subunit, which is the component of CT that is detected in the GM 1 -ELISA assay (Yu et al, 1992). We hypothesized that if tcpG transcription were under ToxT control, then the mutants might be deficient for CT in the culture supernatants, which is what we use for the GM 1 -ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether toxin secretion was affected in the mutants, we analysed their ability to secrete the B subunit of heat-labile toxin (LT ) of E. coli, which is identical in structure to CT and which also requires TcpG(DsbA) to be secreted from V. cholerae (Yu et al, 1992). We introduced pMMB68, which expresses the gene encoding the Immunoblot of TcpA production in wild-type and toxT mutant V. cholerae.…”
Section: Resultsmentioning
confidence: 99%
“…This gene (and, by association, the AE phenotype) is necessary for full virulence in humans, as an eae mutant shows a significantly diminished diarrhoeal attack rate in volunteers relative to the wild-type parent strain (Donnenberg et al, 1993a). Genes homologous to eae have been found in all AE bacteria with the exception of H. pylori, implying a common mechanism of AE lesion formation among these pathogens (Yu et al, 1992;Schauer and Falkow, 1993;Frankel et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…2 To facilitate controlled, high level expression of CtxAB, the EcoRV-SpeI fragment of pRC1 was subcloned into pTTQ18 (35) at the SmaI and XbaI sites to yield pRC9. Plasmid pTRH29 was described previously and is a pBluescript derivative containing the etxAB operon of E. coli enterotoxin flanked by EcoRV and SpeI restriction sites (36). A pTTQ18 derivative, harboring the EcoRV-SpeI fragment from pTRH29 and designated pAM29, has been described (37).…”
Section: Ctx and Etx Operonsmentioning
confidence: 99%
“…Wild-type and hybrid toxins. Plasmid pRC1 contains the entire ctxAB operon encoding wild-type CtxAB; plasmid pTRH29 (36) contains the entire etxAB operon encoding wild-type EtxAB; plasmid pATA14 encoding CtxA (RDEL) CtxB was generated by PCR amplification of upstream and downstream segments of the ctxAB operon followed by their ligation at an engineered EcoRI site to introduce a Lys-237 to Arg substitution; plasmid pRC18 encoding EtxA CtxA (225-240) CtxB was generated by ligating an upstream segment of etxA to a downstream segment of the ctxAB operon at an engineered KpnI site; pRC19 encoding CtxA EtxA (226 -240) EtxB was generated by ligating an upstream segment of ctxA to a downstream segment of the etxAB operon at an engineered KpnI site; and pCDR1 encoding CtxA (RDEL) EtxB was constructed by substituting the EcoRV-EcoRI fragment in pTRH29 for the corresponding fragment from pATA14. In all cases, the vector pBluescript II KS is not depicted.…”
Section: Assessment Of Holotoxin Stabilitymentioning
confidence: 99%